2017
DOI: 10.1007/s11064-017-2298-5
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Pathological Changes in Neurochemical Profile of the Hippocampus and Early Changes in the Olfactory Bulbs of Tau Transgenic Mice (rTg4510)

Abstract: Tauopathies such as Alzheimer’s disease and frontotemporal lobe degeneration (FTLD-tau) dementia, characterized by pathologic aggregation of the microtubule-associated tau protein and formation of neurofibrillary tangles, have been linked to neurodegeneration and cognitive decline. The early detection of cerebral abnormalities and the identification of biological contributors to the continuous pathologic processes of neurodegeneration in tauopathies critically hinge on sensitive and reliable measures of biomar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 44 publications
5
8
0
Order By: Relevance
“…other two brain regions. Indeed, a slower decay of the volume of olfactory bulb than hippocampus at the early and middle stages of AD was reported in rTg510 mice, another AD mice model (Kim et al, 2017). In another study on 5xFAD mice, an intact olfactory memory from 3 to 15 months of age was reported (O'Leary et al, 2020).…”
Section: Discussionmentioning
confidence: 97%
“…other two brain regions. Indeed, a slower decay of the volume of olfactory bulb than hippocampus at the early and middle stages of AD was reported in rTg510 mice, another AD mice model (Kim et al, 2017). In another study on 5xFAD mice, an intact olfactory memory from 3 to 15 months of age was reported (O'Leary et al, 2020).…”
Section: Discussionmentioning
confidence: 97%
“…Whilst on initial inspection this may appear surprising, it likely reflects the paucity of knowledge about brain volume changes in normal rodent aging. Hippocampal volume increases between 5 and 35 weeks of age 38 and 5 and 12 months of age 39 in wild-type mice have been described in different degenerative disease models, including Huntington’s disease and frontotemporal lobe degeneration tauopathy. This increase is presumably due to brain maturation in healthy animals.…”
Section: Discussionmentioning
confidence: 99%
“…Our work demonstrated that trazodone improved olfactory memory during the first month of treatment but did not affect spatial working memory in rTg4510 mice. Impairments in the olfactory system were previously reported in the rTg4510 mice, while olfactory deficits were observed in tau P301S mice when hippocampal-dependent spatial memory was preserved ( Yang et al, 2016 ; Kim et al, 2017 ). This finding is relevant as early olfactory dysfunction is common in Alzheimer's disease ( Hawkes, 2003 ), often occurring prior to other cognitive impairment.…”
Section: Discussionmentioning
confidence: 73%